Market Entry Strategy for LEDON Lamp GmbH - Bihelerová, Judita (2010)
The main goal of this thesis is to set up a vital and pertinent marketing strategy for LEDON Lamp GmbH to enter the UK market with its innovative product. In order to approach the problem correctly, a review of the existing theoretical literature was performed, based on which a thorough secondary and primary research was carried out. The findings include a detailed description of LEDON Lamp GmbH and the UK market, the characteristics of the main competitors, their products and other competing technologies, the possible distribution channels and it also includes a part dealing with the characteristics of British consumers. Furthermore, the research findings are analysed using the tools introduced in the theoretical part of the thesis. Based on those findings and the analysis performed, a market entry strategy and a complete marketing mix are introduced.